Degradation of a hybrid layer – review of literature - Łukomska-Szymańska, Monika; Sokołowski, Jerzy; Łapińska, Barbara (Journal of Stomatology, 2017)
Introduction. The basic premise of adhesive dentistry is to achieve the reliable chemical bond between dental hard tissues and restorative composite material. The hybrid layer is one of the key elements of this interface. Unfortunately, over time the hybrid layer wears out under the influence of physical and chemical factors. As a consequence of this process, marginal leakage forms along the restoration interface, together with marginal discolorations, and even the loss of filling retention. Two following models of hybrid layer degradation were described: disorganization of collagen fibres and hydrolysis (loss) of the resin from the inter-fibrillar spaces within the hybrid layer. Degradation of the collagen matrix requires the coexistence of demineralization and activation of endogenous enzymes present in the dentine. Metalloproteinase of the dentine matrix can be activated by caries or by the application of certain types of bonding systems. Aim of the study. To review up-to-date research results on factors affecting the hybrid layer degradation. Conclusions. Both the type of bonding system and the method of dentine surface treatment have a significant impact on the quality of the hybrid layer, and thus the durability of the resulting adhesive bond. A proper clinical protocol should be established in order to achieve the highest bond strength between the composite material and the dental hard tissue while minimizing degradation with time.